2011
DOI: 10.1161/strokeaha.110.601914
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy as an Emerging Paradigm for Stroke (STEPS) II

Abstract: Abstract-Cell-based therapies represent a new therapeutic approach for stroke. In 2007, investigators from academia, industry leaders, and members of the National Institutes of Health crafted recommendations to facilitate the translational development of cellular therapies as a novel, emerging modality for stroke from animal studies to clinical trials. This meeting was called Stem Cell Therapies as an Emerging Paradigm in Stroke (STEPS) and was modeled on the format of the Stroke Therapy Academic Industry Roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
182
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(193 citation statements)
references
References 17 publications
3
182
0
5
Order By: Relevance
“…This replication meets part of the goals of stroke drug development guidelines (STAIR and STEPS criteria48, 49) and is fairly rigorous in this field in terms of support. There remain additional studies that might enhance these findings, such as testing in other stroke models.…”
Section: The Suffered Is the Learnedmentioning
confidence: 71%
“…This replication meets part of the goals of stroke drug development guidelines (STAIR and STEPS criteria48, 49) and is fairly rigorous in this field in terms of support. There remain additional studies that might enhance these findings, such as testing in other stroke models.…”
Section: The Suffered Is the Learnedmentioning
confidence: 71%
“…The issues include the development of imaging techniques to track the engrafted cells and to monitor the response of the host CNS (10)(11)(12)(13). These techniques would enable validation of the therapeutic benefits of BMSC transplantation without any bias.…”
mentioning
confidence: 99%
“…The first strategy is through donor cell transplantation (from either autologous or allogenic cell sources). Over the last decade, credible data have demonstrated the safety and feasibility of injected stem cells in inducing neural cell regeneration and functional recovery in animal models of stroke, Parkinson's disease, Huntington's disease, and Alzheimer's disease (Gogel et al 2011;Francis and Wei 2010;Haider and Ashraf 2010;Herrmann et al 2010;Savitz et al 2011). Human neural stem cells (HNSCs) transplanted into aged rat brains differentiated into neural cells and significantly improved the cognitive functions of the animals (Sugaya 2005;Sugaya et al 2006;Roitberg et al 2006;Qu et al 2001;Winkler 2001).…”
Section: Stem Cell Therapy Of Neurodegenerative Diseases and Strokementioning
confidence: 99%
“…The second strategy is to enhance endogenous neurogenesis and thus boost endogenous repair mechanisms of the brain (Savitz et al 2011). Much evidence has been found that the brain is capable of regenerating neurons after their maturation (Sugaya 2005;Sugaya et al 2006;Qu et al 2001;Eriksson et al 1998;Allen et al 2001;Aimone et al 2006;Jagasia et al 2006), and stroke can stimulate neurogenesis migration of neural stem/progenitor cells into damaged brain region (Greenberg 2007;Wiltrout et al 2007;Chopp et al 2007;Liu et al 2007).…”
Section: Stem Cell Therapy Of Neurodegenerative Diseases and Strokementioning
confidence: 99%